Application of the Standardized Precipitation Index for Forecasting Seasonal Drought in Vietnam - Long, Trinh Tuan; Van Tan, Phan; Quang Nam, Pham; Thanh Ha, Pham; Anh Quan, Tran; Xuan Thanh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 4DO - 10.25073/2588-1094/vnuees.5184, 2024)
Drought is a natural disaster that causes significant damages to the economy, society and environment. Forecasting droughts is crucial for disaster risk management and water security. This study introduces a new method for forecasting seasonal droughts in Vietnam using the Standardized Precipitation Index (SPI) which is based on a combination of dynamic modeling and statistical methods. The precipitation forecast products from regional climate models (RegCM, clWRF) with inputs from Climate Forecast System (CFSv2) were used to calculate the SPI index after statistical calibration. Results show that calibrating model precipitation with statistical methods such as Artificial Neural Networks (ANN) and Multivariate Linear Regression (MLR) significantly improves the precipitation forecast accuracy. Evaluation indices indicate that the SPI calculated with the post-calibration model precipitation has a good reproducibility for drought events, particularly mild droughts. However, there remains some limitations on accurate forecast of the intensity and spatial distribution of moderate drought events in certain regions such as Central Vietnam.